2017
DOI: 10.1111/jcpt.12501
|View full text |Cite
|
Sign up to set email alerts
|

Drug-drug interaction between valproic acid and meropenem: a retrospective analysis of electronic medical records from neurosurgery inpatients

Abstract: This is the first study using a large number of VPA TDM records to investigate the change in VPA levels caused by concomitant use of MEPM. Our results imply that the decrease in drug concentration cannot be reversed by increasing VPA dose. Moreover, MEPM daily dose did not influence the drop in VPA plasma level. At least 7 days are required for the recovery of VPA plasma concentration after discontinuation of MEPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…There are few case reports describing decreased VPA serum levels by carbapenems (Nacarkucuk et al, 2004;Clause et al, 2005;Fudio et al, 2006;Suntimaleeworakul et al, 2012). A recent study also documented the decreased VPA levels caused by concomitant use of meropenem using a large number of therapeutic drug monitoring (TDM) records (Wen et al, 2017). We present additional two cases of this significant drug interaction.…”
Section: Introductionmentioning
confidence: 73%
“…There are few case reports describing decreased VPA serum levels by carbapenems (Nacarkucuk et al, 2004;Clause et al, 2005;Fudio et al, 2006;Suntimaleeworakul et al, 2012). A recent study also documented the decreased VPA levels caused by concomitant use of meropenem using a large number of therapeutic drug monitoring (TDM) records (Wen et al, 2017). We present additional two cases of this significant drug interaction.…”
Section: Introductionmentioning
confidence: 73%
“…One additional serious interaction to consider as the incidence of multidrug-resistant organisms increases is between carbapenem antibiotics and valproic acid. Numerous potential mechanisms exist to describe this interaction; however, it is believed that carbapanems inhibit an enzyme crucial to the production of the pharmacologically active moiety of valproic acid, resulting in significantly reduced plasma valproic acid concentrations [83,84,85]. In patients on valproic acid, alternatives to carbapenems should be utilized if possible.…”
Section: Special Considerationsmentioning
confidence: 99%
“…Meropenem has been shown to have a favourable safety profile, especially in central nervous system (CNS) tolerability. Therefore, for neurosurgical patients with active seizure disorder, or those who are at a high risk of developing seizures, meropenem is preferred when carbapenem antibiotics are indicated (3). However, a series of reports have indicated that the concomitant use of VPA and carbapenems, especially meropenem, can rapidly reduce the VPA plasma concentration (1,(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for neurosurgical patients with active seizure disorder, or those who are at a high risk of developing seizures, meropenem is preferred when carbapenem antibiotics are indicated (3). However, a series of reports have indicated that the concomitant use of VPA and carbapenems, especially meropenem, can rapidly reduce the VPA plasma concentration (1,(3)(4)(5)(6)(7)(8). In our hospital, pharmacists found that the concomitant use of VPA and carbapenems was not completely avoided, and was accompanied decreased VPA concentration as well as a significantly higher alanine aminotransferase (ALT) value.…”
Section: Introductionmentioning
confidence: 99%